Дослідження стану електрона у потенціальній ямі зі стінками кінцевої висоти - Морозов, Микола Вікторович; Морозов, Николай Викторович; Morozov, Mykola; Халанчук, Лариса Вікторівна; Халанчук, Лариса Викторовна; Khalanchuk, Larysa; Рожкова, Олена Павлівна; Рожкова, Елена Павловна; Pozhkova, Olena; Михайленко, Олена Юріївна; Михайленко, Елена Юрьевна; Mykhailenko, Olena (ТДАТУ, 2020)
UK: Розглянуто математичне, комп’ютерне моделювання стану електронів у прямокутній потенціальній ямі зі стінками кінцевої висоти. Використовується рівняння Шредінгера для знаходження хвильових функцій та власних значень енергії електрона. Застосування граничних умов та чисельних методів послідовних наближень (ітерацій) дозволяє визначити хвильові числа для різних квантових чисел. Для математичного, комп’ютерного моделювання та побудови відповідних графіків хвильової функції та щільності ймовірності знаходження електрона в заданій області прямокутної потенціальної ями використовуються пакети програм Scilab та Mathcad. Результати досліджень застосовують для методичного забезпечення лабораторного практикуму для магістрантів з дисциплін «Фізичні основи сучасних інформаційних технологій» та «Фізико-математичне забезпечення магістерських програм». RU: Рассмотрено математическое, компьютерное моделирование состояния электронов в прямоугольной потенциальной яме со стенками конечной высоты. Используется уравнение Шредингера для поиска волновых функций и собственных значений энергии электрона. Применение граничных условий и численных методов последовательных приближений (итераций) позволяет определить волновые числа для разных квантовых чисел. Для математического, компьютерного моделирования и построения соответствующих графиков волновой функции и плотности вероятности нахождения электрона в заданной области прямоугольной потенциальной ямы используются пакеты программ ScilabиMathcad. Результаты исследований применяют для методического обеспечения лабораторного практикума для магистрантов по дисциплине «Физические основы современных информационных технологий» и «Физико-математическое обеспечение магистерских программ». EN: Quantum systems are widely used in the technical support of modern information technologies. Therefore, the development and research of mathematical, computer models of heterosystems, which are extremely small, is an urgent task. The use of the Schrödinger equation for stationary states of the wave function and the consideration of the influence of the parameters of the 1D potential well on the spectrum of the eigenvalues of the electron energy are of considerable interest. Mathematical, computer modeling of the state of electrons in a rectangular potential well with walls of finite height is considered. Quantum potential wells are obtained on the basis of heterostructures, for example, AℓGaAs - GaAs - AℓGaAs. A heterostructure is a layered structure of semiconductors that have different band gaps. The Schrödinger equation is used to find the wave functions and the eigenvalues of the electron energy. The application of boundary conditions and numerical methods of successive approximations (iterations) allows to determine wave numbers for different quantum numbers. The wave functions, probability density and eigenvalues of energy for different electron states are obtained. The dependence of discrete electron levels on the parameters of the potential well: width and depth is investigated. Numerical methods for solving the equations of boundary conditions for the electron wave function, probability density, and the algorithm for plotting have been developed. Scilab and Mathcad software packages are used for mathematical, computer modeling and construction of appropriate graphs of the wave function and the density of the probability of finding an electron in a given area of a rectangular potential well. The research results are used for methodological support of laboratory workshops for undergraduates in the disciplines "Physical foundations of modern information technology" and "Physical and mathematical support of master's programs".
Исследование состояния электрона в потенциальной яме со стенками конечной высоты
Research of theelectron state in a potential pit with finite height walls
Keywords: потенціальна яма кінцевої глибини; математичне моделювання; комп’ютерне моделювання; власна енергія; дискретні моделі; потенциальная яма конечной глубины; математическое моделирование; компьютерное моделирование; собственная энергия; дискретные модели; mathematical; potential pit of finite depth; computer modeling; self-energy; discrete models